Kościół katolicki wobec reform szpitalnictwa u schyłku I. Rzeczypospolitej - Srogosz, Tadeusz (Saeculum Christianum. Pismo Historyczne, 2020)
In individual cases of hospitals, we can see a far-reaching convergence of views, especially when this did not significantly affect the interests of groups or institutions. However, there were extremely fierce disputes over the proposals that undermined the monopolistic position of the Church and its income. During the Four-Year Sejm, anticlerical tendencies intensified. The Authorities of the Four-Year Sejm tried to solve the problem of hospital funds, repeatedly raised in the 18th century (and earlier), but – a.o., due to the resistance of some clergymen - they managed to gather only some information from hospital managers. The activities of the authorities with regard to the hospitals tentatively aimed at their medicalisation, whereas the Church, in its mainstream, adhered to inalterability of social care and opposed any interference or change.